In Situ Investigations of Mechanochemical One‐Pot Syntheses. Issue 20 (17th April 2018) - Kulla, Hannes; Haferkamp, Sebastian; Akhmetova, Irina; Röllig, Mathias; Maierhofer, Christiane; Rademann, Klaus; Emmerling, Franziska
Abstract: We present an in situ triple coupling of synchrotron X‐ray diffraction with Raman spectroscopy, and thermography to study milling reactions in real time. This combination of methods allows a correlation of the structural evolution with temperature information. The temperature information is crucial for understanding both the thermodynamics and reaction kinetics. The reaction mechanisms of three prototypical mechanochemical syntheses, a cocrystal formation, a C−C bond formation (Knoevenagel condensation), and the formation of a manganese‐phosphonate, were elucidated. Trends in the temperature development during milling are identified. The heat of reaction and latent heat of crystallization of the product contribute to the overall temperature increase. A decrease in temperature occurs via release of, for example, water as a by‐product. Solid and liquid intermediates are detected. The influence of the mechanical impact could be separated from temperature effects caused by the reaction. Abstract : Three strikes in one stroke : Synchrotron X‐ray diffraction, Raman spectroscopy, and thermography are coupled to study ball milling mechanochemistry reactions in real time. This combination allows the structural evolution to be correlated with temperature information. The temperature information is crucial for understanding both the thermodynamics and reaction kinetics.